Piercing the bamboo curtain : Tentative bridge-building to China during the Johnson years - Lumbers, Michael (Book collections on Project MUSE., 2008)
A comprehensive account of the Johnson administration's China policy. The book links Johnson's China policy to the Vietnam War and the Cultural Revolution and traces the development of U.S. approaches to China during a critical period of the Cold War.